Determinants of Islamic Religious Education Learning and the Role of Islamic Religious Education Teachers in Fostering Students’ Social Awareness to Prevent Bullying in Schools - Atika Nailah Syirva; Zaenal Arifin; Ahmad Badi'; Hanim Misbah (Yayasan Adra Karima Hubbi, 2026)
Background. Bullying remains a serious problem in educational settings because it has a negative impact on students’ psychological well-being, character development, and the learning environment. Although various studies have examined bullying prevention, there are still few studies that integrate the intensity of Islamic Religious Education (IRE) instruction and the role of IRE teachers in fostering students’ social awareness as a means of preventing bullying, particularly at Al-Kamal Junior High School in Blitar. Purpose. This study aimed to analyze the contribution of the intensity of Islamic Religious Education learning and the role of PAI teachers in enhancing students’ social awareness in avoiding bullying behavior. Method. This study employed a quantitative approach with a correlational design. The population consisted of all 336 students of SMP Al-Kamal Blitar, with a sample of 50 students selected using a random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression and the coefficient of determination tests to examine both partial and simultaneous effects of the independent variables. Results. The findings revealed that both the intensity of Islamic Religious Education learning and the role of PAI teachers have a significant influence, both partially and simultaneously, on students’ social awareness in avoiding bullying. These results indicate that stronger learning intensity and active teacher involvement contribute positively to shaping students’ social sensitivity and behavior. Conclusion. This study highlights the importance of integrating structured PAI learning with the professional roles of teachers in preventing bullying through the development of students’ social awareness. It also offers theoretical contributions by reinforcing the integration of social learning theory, moral development theory, and Islamic education. Practically, it recommends strengthening character-based educational policies and encourages future research to adopt longitudinal or mixed-method approaches for more comprehensive insights.